Diet in treatment of autism spectrum disorders - Alam, Sabiha; Westmark, Cara J.; McCullagh, Elizabeth A. (Frontiers in Neuroscience, 2023)
Altering the diet to treat disease dates to c. 400 BC when starvation was used to reduce seizures in persons with epilepsy. The current epidemic of autism spectrum disorders (ASDs) and a corresponding lack of disease-specific effective treatments prompts an evaluation of diet as a therapeutic approach to improve symptoms of ASDs. In this review article, we summarize the main findings of nutritional studies in ASDs, with an emphasis on the most common monogenic cause of autism, Fragile X Syndrome (FXS), and the most studied dietary intervention, the ketogenic diet as well as other dietary interventions. Our review of the literature shows that diet as an intervention is still a relatively underexplored area of research, particularly in FXS, and that the studies that have been conducted indicate that it may be a relevant area for future studies. We also discuss the gut microbiota in relation to pre- and probiotic therapies and provide insight into future directions that could aid in understanding the mechanism(s) underlying dietary efficacy.